Clinical conditions and history of illness among terminal chronic kidney disease patients - Titiek Hidayati; Arya Adiningrat; Akrom Akrom (International Journal of Public Health Science (IJPHS), 2019)
End-stage renal disease (ESRD) is one of the public health problems in Indonesia. This study aimed to determine the clinical condition of premorbid and the incidence of ESRD. The study design is a case-control. The number of volunteers involved in this study was 100 patients. The cases were ESRD patients who were determined by the criteria of Pernefri and the controls were patients from the same hospital who were not ESRD by the requirements of ESRD Pernefri. Inclusion criteria of the study sample were ESRD sufferers need routine hemodialysis and doctor's diagnosis supported by laboratory data, 15-75 years old and willing to fill out inform consent. Exclusion criteria for the study sample were patients with congenital kidney disease, Have a history of kidney transplants, and mental disorder. We collected demographic data, and patient’s clinical and drug history from medical records. Chi-square analysis with 2x2 tables and the Fisher's exact test were used to determine the relationship of clinical conditions and history of disease with the incidence of ESRD. The results showed that anemia, hyperglycemia, and hypertriglyceridemia were related to the prevalence of ESRD. History of hypertension, diabetes mellitus, dyslipidemia, and family history of ESRD are associated with an increased incidence of ESRD.